Penerapan Manajemen Kelas pada Pembelajaran Pendidikan Agama Kristen Berbasis Kurikulum Merdeka - Betieli Gulo (Sekolah Tinggi Alkitab Batu, Malang, 2024)
The classroom is the center for all aspects of learning to meet and process. The classroom is a place that allows students to freely learn with efforts made by the teacher which is known as classroom management. However, it is found that many teachers are unable to differentiate between classroom management and teaching activities. Teachers only know how to teach but have weaknesses in managing the class. Teachers should be able to manage the class by looking at elements in teaching such as student background, curriculum used, methods, media and teaching materials. The learning curriculum merdeka is being hotly discussed and recommended by the government to be applied to learning, including in the field of study of Christian Religious Education. Implementing the learning curriculum merdeka in Christian religious education is both a challenge and a necessity through good classroom management skills. This research uses a qualitative method, where the findings are analyzed and then described in sentences. The research results found that teachers who understand classroom management will find it easier to implement an curriculum merdeka, students will have more freedom to learn because learning is in accordance with their comfortable position, and the teacher's expertise in managing the classroom will make it easier to achieve learning goals and increase students' interest in learning Christian Religious Education . ABSTRAKKelas merupakan pusat segala aspek pembelajaran bertemu dan berproses. Kelas merupakan tempat yang memungkinkan siswa bebas belajar dengan upaya yang dilakukan oleh guru yang disebut sebagai manajemen kelas. Tetapi, banyak ditemukan guru tidak mampu membedakan antara manajemen kelas dengan kegiatan mengajar. Guru hanya mengetahui bagaimana mengajar tetapi memiliki kelemahan mengelola kelas. Guru harusnya mampu mengelola kelas dengan melihat elemen dalam mengajar seperti latarbelakang siswa, kurikulum yang digunakan, metode, media, dan bahan ajar. Kurikulum merdeka belajar sedang hangat diperbincangkan dan dianjurkan oleh pemerintah untuk diterapkan pada pembelajaran, termasuk pada bidang studi Pendidikan Agama Kristen. Penerapan kurikulum merdeka belajar dalam pendidikan agama Kristen merupakan sebuah tantangan sekaligus keharusan melalui kemampuan mengelola kelas yang baik. Penelitian ini menggunakan metode kualitatif, dimana hasil temuan dianalisa lalu dideskripsikan dalam kalimat. Hasil penelitian ditemukan bahwa guru yang memahami manajemen kelas akan lebih mudah menerapkan kurikulum merdeka, siswa lebih leluasa untuk belajar karena pembelajaran sesuai dengan posisi kenyamanan mereka. Kepiawaian guru dalam mengelola kelas akan memberi kemudahan pada pencapaian tujuan pembelajaran serta meningkatkan minat belajar siswa pada pembelajaran Pendidikan Agama Kristen. Kata Kunci : Manajemen; Kelas; Pembelajaran PAK; Kurikulum Merdeka Belajar